2020
DOI: 10.1002/admt.202000286
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Composites Containing Phase‐Change Microcapsules Displaying Deep Undercooling Exhibit Thermal History‐Dependent Mechanical Properties

Abstract: they melt into a liquid and releasing heat as they solidify into a solid. The greater the latent heat of fusion, the greater the energy absorbed/released during these phase transitions. [5,6] As various groups have shown, by encapsulating micron to millimeter diameter droplets of a PCM, functionalities ranging from temperaturedependent permeability to enhanced solar thermal energy storage efficiency can be realized. [7,8] Once encapsulated, PCMs can be embedded in a diversity of matrices, which may enable new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In conclusion, complete grain refinement at large undercooling has strong texture and annealing twins. Recrystallization is driven by deformation energy, and new deformation free grains are formed in the deformed matrix through the formation and subsequent migration of large angle grain boundaries [14]. Due to solidification of undercooled melt, the lattice distortion caused by solute capture and dendrite deformation can store deformation energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, complete grain refinement at large undercooling has strong texture and annealing twins. Recrystallization is driven by deformation energy, and new deformation free grains are formed in the deformed matrix through the formation and subsequent migration of large angle grain boundaries [14]. Due to solidification of undercooled melt, the lattice distortion caused by solute capture and dendrite deformation can store deformation energy.…”
Section: Resultsmentioning
confidence: 99%
“…Grain refinement mechanism of undercooled solidification microstructure of binary alloys is a topic of debate for decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. For highly undercooled single phase binary alloys, recent studies on Fe-Ni [3], Ni-Cu [4], Fe-Co [6] and Ni-C [9] alloys show that two grain refinement could be found.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, swelling disrupts the order of structure and increases heterogeneity of internal structures of polymer, and thus significant changes in structure and mechanical properties happen after 2 days of the elastomer immersed in various liquids. 9,10 Rubber products used in oil industry appear severe changes in mechanical properties under the conditions of continuous rotation, shear stress and extrusion stress. [11][12][13] In practice, the swelling process can be promoted by the aggressive media, extraction of small additives and chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…When the initial undercooling degree of the alloy melt is greater than a certain critical value, the solidification structure changes from developed dendrites to fine equiaxed crystals, and the grain size decreases by about 2 orders of magnitude [1][2][3][4][5][6][7][8][9][10] . Kattamis et al found that CuNi alloy presents developed dendrites when undercooling is less than 175 K and fine equiaxed crystals when undercooling is greater than 175 K. Recently, some researchers [4,[11][12][13][14] found that the grain refinement phenomenon of columnar dendrite to equiaxed crystal also exists under small undercooling.…”
Section: Introductionmentioning
confidence: 99%